Revenue Potential and Revenue Efforts of Southern States - Planning Commission (Planning Commission, 1979)
India is undoubtedly a federation as far as the fiscal powers of Government are concerned. Though judging by the overall constitutional structure it is called a quasi-federation, from the point of view of the power to raise revenue and the power to spend it, the responsibility has been constitutionally divided between the Union and the State Governments. Both the Union and the State Governments enjoy exclusive as well as concurrent powers. This fiscal federalism has acquired significance through the recommendations of the Finance Commission. The Finance Commission, which has been provided for in the Constitution, recommends quinquennially the financial transfers from the Union Government to the State Governments to facilitate the effective operation of the fiscal federalism. Even beyond this fiscal sphere, India is becoming an effective federation in view of the reorganisation of the States on linguistic basis, and the recent political awareness created by the 1977 parliamentary elections. After the reorganisation, the States started asserting their independent cultural autonomy centred around their languages and after the 1977 elections different political parties which came into power in some States have revived the idea of true federalism.
A Study Sponsored by the Planning Commission, Government of India
A Study Sponsored by the Planning Commission, Government of India